State of the art(s) education an investigative study on the implementation of the special program in the arts in the National Capital Region - Camba, Meeko Angela Ronquillo 1996-; Khan, Rachel E., Ph.D (2018)
"This report examines the current state of public high schools in the National Capital Region implementing the country's sole art education program, with the Mariano Marcos Memorial High School (MMMHS) as the main case study. Established in 2000, the Special Program in the Arts (SPA) was first implemented by the Department of Education (DepEd) in 15 pioneer schools nationwide to nurture artistically inclined students to become bearers of Filipino culture and heritage. But 18 years and over 200 SPA school later, this report reveals how DepEd has ultimately failed to ensure that the program meet implementation standards, as stated in Department Order No. 135, series of 2001 or the SPA Implementing Guidelines. Hampered by DepEd's crucial lapses in monitoring and ineffective feedback system, as well as the lack of qualified teachers, among other issues, SPA implementation across the region has been inconsistent at best. In MMMHS, a pioneer school,teachers and students struggle to make-do with subpar learning facilities and equipment, now non-existent funding, and limited books and other resources. Such findings have proven to be more urgent now that the K-12 curriculum is about to reach its third year, with enrollees in the Art and Design track, SPA's counterpart in the senior high school level, making up less than one percent of over 700,000 senior high school students in 2016. The story is presented in a three-part long-form investigative report, enhanced with photos and data visualization. Part I tackles the current situation of MMMHS, the region's pioneer SPA school, highlighting issues in implementation such as the lack of qualified teachers and insufficient funding. Part II focuses on DepEd's lapses in monitoring, as well as outdated policies that have hindered the progress of the SPA. Finally, the third part discusses the department's plans for the SPA's future in light of the current Philippine Development Plan."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Art -- Study and teaching -- Manila Metropolitan Area; Mariano Memorial High School